Effect of temperature and time on indicators of potato (Solanum tuberosum), fermented in solid state - Borras-Sandoval, Luis Miguel; Iglesias, Arabel Elías; Moyano-Bautista, Mónica Andrea (Universidad Pedagógica y Tecnológica de Colombia, 2014)
This paper evaluate the effect of the temperature and incubation time in some fermentative indicators of potato subjected to solid-state fermentation. We used a completely random design with factorial arrangement: three temperature treatments (20°, 25° and 30 °C) and two time treatments (24 and 48 hours), with three replicates for each one. We mixed fresh chopped potatoes with a drying agent, molasses, urea, effective microorganisms, mineral premix and sodium sulfate; and we placed the mixture in 1 Kg plastic bags to ferment according to the time and temperature treatments. The Fespotato product incubated at different temperatures showed significant changes (P <0.01) in the evaluated fermentative indicators. The pH declined steadily since the beginning (pH 5.7) to the end of the assessment after 48 hours (pH 4.4) regardless of the incubation temperature. Similarly, the ammonia concentration (NH3-N) and total volatile fatty acids (AGVt) decreased with fermentation time related to the decrease of pH. The dry matter (DM) content increased (19.3 to 38.5%) with the raise in temperature at 24 hours, whereas it decreased at 48 hours (38.1 to 17.9%). The Fes-papa is a simple biotechnological process that takes advantage of the tubers crop residues to generate an energy-protein food, which according to the fermentative and content in MS indicators could be used in animal feed in addition to counter environmental pollution.